2017
DOI: 10.1002/2016jd026326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environment forcing on marine boundary layer cloud‐drizzle processes

Abstract: Determining the factors affecting drizzle formation in marine boundary layer (MBL) clouds remains a challenge for both observation and modeling communities. To investigate the roles of vertical wind shear and buoyancy (static instability) in drizzle formation, ground‐based observations from the Atmospheric Radiation Measurement Program at the Azores are analyzed for two types of conditions. The type I clouds should last for at least 5 h and more than 90% time must be nondrizzling and then followed by at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 105 publications
2
28
0
Order By: Relevance
“…Of broader interest here is identifying other factors that could drive precipitation variability, which may also further help explain the differences in precipitation characteristics observed between PCF and non‐PCF subsidence conditions. Monotonic relationships are identified between a number of large‐scale parameters and rain properties: Higher sea‐air temperature contrast and higher surface horizontal wind speed are both associated with higher RCF CB and (RR CB ), higher EIS is found to relate to higher RCF CB (as speculated by Kubar et al, 2009) and, higher Estimated Inversion Strength (EIS) is also to some extent found to relate to lower RR CB (in general agreement with Wu et al, 2017), although higher M parameter (also a measure of atmospheric stability) was found to have a much more consistent relationship. Lower correlations between both cloud and rain properties with EIS perhaps relate to the fact that some of the observed clouds are advected rather than locally formed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of broader interest here is identifying other factors that could drive precipitation variability, which may also further help explain the differences in precipitation characteristics observed between PCF and non‐PCF subsidence conditions. Monotonic relationships are identified between a number of large‐scale parameters and rain properties: Higher sea‐air temperature contrast and higher surface horizontal wind speed are both associated with higher RCF CB and (RR CB ), higher EIS is found to relate to higher RCF CB (as speculated by Kubar et al, 2009) and, higher Estimated Inversion Strength (EIS) is also to some extent found to relate to lower RR CB (in general agreement with Wu et al, 2017), although higher M parameter (also a measure of atmospheric stability) was found to have a much more consistent relationship. Lower correlations between both cloud and rain properties with EIS perhaps relate to the fact that some of the observed clouds are advected rather than locally formed.…”
Section: Discussionsupporting
confidence: 81%
“…i Higher sea-air temperature contrast and higher surface horizontal wind speed are both associated with higher RCF CB and (RR CB ), ii higher EIS is found to relate to higher RCF CB (as speculated by Kubar et al, 2009) and, iii higher Estimated Inversion Strength (EIS) is also to some extent found to relate to lower RR CB (in general agreement with Wu et al, 2017), although higher M parameter (also a measure of atmospheric stability) was found to have a much more consistent relationship. Lower correlations between both cloud and rain properties with EIS perhaps relate to the fact that some of the observed clouds are advected rather than locally formed.…”
Section: 1029/2019jd031848supporting
confidence: 68%
“…For example, VWS influences the rainfall and total condensation within developing convection (Weisman and Rotunno, 2004), slantwise ascent of the parcel (Moncrieff, 1978), storm rotation, maintenance, vorticity, updraft speed (Weisman and Rotunno, 2000), and lifetime (Chakraborty et al, 2016). Though detailed microphysical properties are not considered in our simple plume calculations, it is worth noting that a recent study by Wu et al (2017) found that lower tropospheric wind shear promotes the droplet collision and growth inside the shallow clouds by the production of turbulent kinetic energy. However, Weisman and Rotunno (2004) using a two-dimensional vorticity simulation model found that increasing vertical wind shear depth from surface −3 km (low) to surface −10 km (deep) decreases the overall condensation and rainfall output.…”
Section: Examining Indirect Thermodynamic Effects From Shear and Ccn mentioning
confidence: 99%
“…Stratocumulus clouds cover large areas in subtropical and tropical ocean regions and play an important role in Earth's radiation budget (Lamb & Verlinde, 2011). Drizzle drops, generating light precipitation, are frequently observed below marine stratocumulus clouds (e.g., Glienke et al, 2017;Leon et al, 2008;Rémillard et al, 2012;Wu et al, 2017). The initiation, growth, and depletion of drizzle play crucial roles in the stratocumulus-topped boundary layer and have been studied extensively (Wood, 2012).…”
Section: Introductionmentioning
confidence: 99%